2022
DOI: 10.1039/d2fo01646j
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical properties and bioactivity of polysaccharides from Isaria cicadae Miquel with different extraction processes: effects on gut microbiota and immune response in mice

Abstract: The effect of different extraction processes on the physicochemical characterization, digestibility, antioxidant and prebiotic activity of Isaria cicadae Miquel fruiting body polysaccharides (ICM) was studied in this paper. Furthermore, the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…Wang W et al [ 37 ] found that when healthy mice were fed Isaria cicadae Miquel (ICM) fruiting body polysaccharides, the relative abundances of Lactobacillus , Akkermansia , and Bacteroides were found to increase significantly, while that of Clostridium decreased significantly. Some researchers have used black raspberry anthocyanins as a dietary supplement to enhance the growth of Eubacterium rectum , Faecalibacterium prausnitzii , and Lactobacillus and inhibit the growth of Desulfovibrio and Enterococcus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang W et al [ 37 ] found that when healthy mice were fed Isaria cicadae Miquel (ICM) fruiting body polysaccharides, the relative abundances of Lactobacillus , Akkermansia , and Bacteroides were found to increase significantly, while that of Clostridium decreased significantly. Some researchers have used black raspberry anthocyanins as a dietary supplement to enhance the growth of Eubacterium rectum , Faecalibacterium prausnitzii , and Lactobacillus and inhibit the growth of Desulfovibrio and Enterococcus [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunofluorescence of Tight Junction Protein and Mucoprotein. The immunofluorescence determination of ZO-1, Claudin-1, and MUC-2 in ileum tissue was described by Wang et al 10 Spontaneous fluorescence quench agent was added to the tissue sections and kept for 5 min. Then, 3% bovine serum albumin was added to the tissue sections for incubation for 30 min, and primary antibody (1:100, rabbit polyclonal anti-ZO-1, anti-Claudin-1, anti-MUC-2) was added to the sections and incubated overnight in a wet box at 4 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Prebiotics are defined as selective fermentation components that can be utilized by the intestinal microbiota and modulate the intestinal microbiota to promote host health. 10 Because the dysbiosis of the intestinal microbiota due to alcohol exposure is often accompanied by nutritional deficiencies, probiotics may have difficulty obtaining desirable metabolic substrate from the intestinal of ALD patients. Therefore, the combined application of probiotics and prebiotics (synbiotics) targeting intestinal microecology may be an effective solution to alleviate ALD.…”
Section: ■ Introductionmentioning
confidence: 99%
“…7 Due to the dynamic imbalance between ROS and antioxidant defense, it ultimately leads to oxidative stress and lipid peroxidation in hepatocytes. 8,9 Furthermore, long-term alcohol intake leads to intestinal dysbiosis and accumulation of intestinal endotoxins. Although most of the absorbed ethanol is metabolized in the liver, alcohol dehydrogenase (ADH) is also expressed in intestinal epithelial cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Excessive ROS leads to a dynamic imbalance of the antioxidant system centered on the antioxidant regulatory gene Nrf-2 and downregulates downstream antioxidant genes including superoxide dismutase (SOD), catalase (CAT), and glutathione (GSH) . Due to the dynamic imbalance between ROS and antioxidant defense, it ultimately leads to oxidative stress and lipid peroxidation in hepatocytes. , …”
Section: Introductionmentioning
confidence: 99%